2020
DOI: 10.1021/acscatal.0c03440
|View full text |Cite
|
Sign up to set email alerts
|

Acridine Photocatalysis: Insights into the Mechanism and Development of a Dual-Catalytic Direct Decarboxylative Conjugate Addition

Abstract: Conjugate addition is one of the most synthetically useful carbon–carbon bond-forming reactions; however, reactive carbon nucleophiles are typically required to effect the addition. Radical conjugate addition provides an avenue for replacing reactive nucleophiles with convenient radical precursors. Carboxylic acids can serve as simple and stable radical precursors by way of decarboxylation, but activation to reactive esters is typically necessary to facilitate the challenging decarboxylation. Here, we report a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…12,22,24 A related class of reactions that utilize N-(acyloxy)phthalimides (or NHPI esters) involve decarboxylative alkyl additions to alkynes 25 or alkenes. [26][27][28][29][30][31][32][33][34][35][36][37] Intrigued by previous studies, we speculated if alkyl NHPI esters could be exploited in three-component processes by merging with an alkyne and an alkynyl halide to deliver synthetically valuable acyclic 1,3-enyne motifs, conjugated entities commonly embedded within natural products, pharmaceuticals, agrochemicals and materials. [38][39][40][41][42]…”
mentioning
confidence: 88%
“…12,22,24 A related class of reactions that utilize N-(acyloxy)phthalimides (or NHPI esters) involve decarboxylative alkyl additions to alkynes 25 or alkenes. [26][27][28][29][30][31][32][33][34][35][36][37] Intrigued by previous studies, we speculated if alkyl NHPI esters could be exploited in three-component processes by merging with an alkyne and an alkynyl halide to deliver synthetically valuable acyclic 1,3-enyne motifs, conjugated entities commonly embedded within natural products, pharmaceuticals, agrochemicals and materials. [38][39][40][41][42]…”
mentioning
confidence: 88%
“…To address these issues, Larionov and co-workers recently devised a mild dual-catalytic system to facilitate the direct DGR of carboxylic acids without the need for pre-activation by deprotonation. 110 Employing their recently described new class of 9-arylacridine photocatalysts, 111 Acr-3 or Acr-4 were coupled with an efficient Cu( i )/Cu(0) catalytic cycle to access an impressive array of Giese adducts (Scheme 46A). Moderate to excellent yields were obtained for a variety of primary ( 120b , 81%), secondary ( 121 , 76%) and tertiary ( 120a, c–f , and 122 , 52–83%) carboxylic acids with good functional group tolerance for halogens and (un)saturated heterocycles.…”
Section: Photocatalysismentioning
confidence: 99%
“…Recently, Stolarczyk and co‐workers showed that an acridine carbon dot heterostructure can be used for photocatalytic water splitting [41] . Homogeneous acridines have been explored in dual photocatalysis for decarboxylative N ‐alkylation, decarboxylative conjugate addition or dehydrocarboxylation of carboxylic acids [42–44] . Further, it has been observed that acridine based small molecules and materials can harvest lower energetic light radiation compared to anthracene compounds, especially in its protonated form [40, 41, 45] .…”
Section: Introductionmentioning
confidence: 99%